Stochastic stability analysis of integral non-homogeneous Markov jump systems - Yin, YanYan; Zhu, L.; Zeng, H.; Liu, Y.; Liu, F. (Taylor and Francis, 2017)
This paper investigates the problem of stability analysis for time-delay integral Markov jump systems with time-varying transition rates. Some free-weight matrices are addressed and sufficient conditions are established under which the system is stochastically stable. The bound of delay is larger than those in other results obtained, which guarantees that the proposed conditions are tighter. Numerical examples show the effectiveness of the method proposed.